Design and acceptability of patient-oriented computerized diabetes care reminders for use at the point of care. - Sciamanna, C.N.
Despite the widespread availability of guidelines for caring for patients with diabetes and decades of research on computerized reminder systems, large gaps in quality remain in diabetes care remain and computerized reminder systems are rarely used for patients with diabetes. We set out to develop and test of the feasibility of a system that would overcome many of the barriers preventing the widespread use of point-of-care computerized reminders to improve diabetes care. Five primary care physicians and 32 patients with type 2 diabetes pilot tested the system. We set out to design and measure the preliminary acceptability of patient-oriented point of care computerized diabetes care reminders. The main findings of our study were that (1) the reports were well accepted by both patients and providers and (2) survey and audiotape date suggest that they may be helpful at improving the quality of outpatient care for patients with diabetes.
Keywords: Diabetes; Quality; Informatics; Reminders; Primary care